Contribution of 5-HT(2) Receptors to the Control of the Spinal Locomotor System in Intact Rats - Majczyński, Henryk (Front Neural Circuits, 2020)
Applying serotonergic (5-HT) agonists or grafting of fetal serotonergic cells into the spinal cord improves locomotion after spinal cord injury. Little is known about the role of 5-HT receptors in the control of voluntary locomotion, so we administered inverse agonists of 5-HT(2) (Cyproheptadine; Cypr), 5-HT(2A) neutral antagonist (Volinanserin; Volin), 5-HT(2C) neutral antagonist (SB 242084), and 5-HT(2B/2C) inverse agonist (SB 206553) receptors intrathecally in intact rats and monitored their effects on unrestrained locomotion. An intrathecal cannula was introduced at the low thoracic level and pushed caudally until the tip reached the L2/L3 or L5/L6 spinal segments. Locomotor performance was evaluated using EMG activity of hindlimb muscles during locomotion on a 2 m long runway. Motoneuron excitability was estimated using EMG recordings during dorsi- and plantar flexion at the ankle. Locomotion was dramatically impaired after the blockage of 5-HT(2A) receptors. The effect of Cypr was more pronounced than that of Volin since in the L5/L6 rats Cypr (but not Volin) induced significant alteration of the strength of interlimb coordination followed by total paralysis. These agents significantly decreased locomotor EMG amplitude and abolished or substantially decreased stretch reflexes. Blocking 5-HT(2B/2C) receptors had no effect either on locomotion or reflexes. We suggest that in intact rats serotonin controls timing and amplitude of muscle activity by acting on 5-HT(2A) receptors on both CPG interneurons and motoneurons, while 5-HT(2B/2C) receptors are not involved in control of the locomotor pattern in lumbar spinal cord.